Topical Application of Connexin43 Hemichannel Blocker Reduces Carotid Body-Mediated Chemoreflex Drive in Rats - Andrade, David C.; Iturriaga, Rodrigo; Toledo, Camilo; Lucero, Claudia M.; Diaz, Hugo S.; Arce-Alvarez, Alexis; Retamal, Mauricio A.; Marcus, Noah J.; Alcayaga, Julio; Del Rio, Rodrigo (My University, 2018)
The carotid body (CB) is the main arterial chemoreceptor involved in oxygen sensing. Upon hypoxic stimulation, CB chemoreceptor cells release neurotransmitters, which increase the frequency of action potentials in sensory nerve fibers of the carotid sinus nerve. The identity of the molecular entity responsible for oxygen sensing is still a matter of debate; however several ion channels have been shown to be involved in this process. Connexin-based ion channels are expressed in the CB; however a definitive role for these channels in mediating CB oxygen sensitivity has not been established. To address the role of these channels, we studied the effect of blockers of connexin-based ion channels on oxygen sensitivity of the CB. A connexin43 (Cx43) hemichannel blocking agent (CHBa) was applied topically to the CB and the CB-mediated hypoxic ventilatory response (F(i)O(2 )21, 15, 10 and 5%) was measured in adult male Sprague-Dawley rats (similar to 250 g). In normoxic conditions, CHBa had no effect on tidal volume or respiratory rate, however Cx43 hemichannels inhibition by CHBa significantly unpaired the CB-mediated chemoreflex response to hypoxia. CHBa reduced both the gain of the hypoxic ventilatory response (HVR) and the maximum HVR by similar to 25% and similar to 50%, respectively. Our results suggest that connexin43 hemichannels contribute to the CB chemoreflex response to hypoxia in rats. Our results suggest that CB connexin43 hemichannels may be pharmacological targets in disease conditions characterized by CB hyperactivity.
Keywords: carotid body; chemoreflex; connexin43; hypoxia